Surface Characteristics and Photocatalytic Gas Degradation of Nonmetal Element-Doped Titania - Jo, Wan-Kuen (Asian Journal of Chemistry, 2013)
The present study explored the characteristics and the photocatalytic activities of S-doped TiO2 (S-TiO2) and N-doped TiO2 (N-TiO2) for the decomposition of gas-phase isopropyl alcohol, according to calcination temperatures. The characteristics of the prepared photocatalysts were determined using an X-ray diffractometer, a scanning electron microscope, a diffuse reflectance ultraviolet-visible-near infrared spectrophotometer, and a Fourier-transform infrared spectrometer. The average degradation efficiency of isopropyl alcohol by the S-TiO2 calcined at 350 ºC was 40 %, whereas it was 98 % for the S-TiO2 calcined at 550 ºC. However, the average degradation efficiency of isopropyl alcohol decreased to 92 % when the calcination temperature was further increased from 550 to 650 ºC. The average degradation efficiency of isopropyl alcohol by the N-TiO2 calcined at 350 ºC was 93 %, whereas it was close to 100 % for the N-TiO2 calcined at 550 and 650 ºC. Moreover, the acetone generation yields as determined using the S- and N-TiO2 were 86 and 58 %, respectively, for the calcination temperature of 350 ºC, whereas they were 78 and 69 %, respectively, for the calcination temperature of 650 ºC. Consequently, as-prepared S-TiO2 and N-TiO2 photocatalysts could be applied to purification of airborne isopropyl alcohol under visible-light irradiation, but the formation of acetone should be considered for their applications.